CIUCIULENI – SATUL CU DOUĂ BISERICI ORTODOXE - Cerga, Alexandru; Bulmaga, Mihail (Biblioteca Științifică Centrală„Andrei Lupan”, 2019)
The history of the villages from the Romanian space is inseparable from the his- tory of the churches from the rural areas, an institution that was for the Romanian peasants, especially those in Bessarabia, the fundamental support for their survival and the continuation of the Romanianism. The study addresses the history of the vil- lage Ciuciuleni in the current Hâncești district, from the perspective of the two Or- thodox churches in this locality – the Church „Sf. Ierarh Nicolae” and the „Sfântul Mare Mucenic Gheorghe” Church. The first Orthodox place, documented for the first time in the second half of the eighteenth century, rebuilt several times over the centu- ries, proved by the beginning of the twentieth century for the many inhabitants of the village. Thus, in 1911, the second church was erected on the north side of the village with the dedication of Saint George the Great. The stages of construction, the paro- chial activity, data on the old Romanian books of worship in churches, as well as the succession of the priestly priests are addressed.
Ciuciuleni – the village with two orthodox churches
Keywords: Ciuciuleni; church